Environmental concentration PFOS as a light shield for lake exopolymers against photodegradation by formation of sandwiched supramolecular nanostructures. (1st December 2022) - Xu, Shuyan; Zhu, Pengfeng; Wang, Caiqin; Zhang, Daoyong; Pan, Xiangliang
Highlights: Environmental concentration PFOS triggered phase separation of EPS. Supramolecular interaction of EPS and PFOS formed sandwich nanostructures. The first visualization of EPS-PFOS nanostructures by nanospectroscopy. PFOS inhibited EPS photodegrdation by its light-shielding effect and PFOS-EPS sandwich structure. Environmental concentration PFOS may profoundly affect aquatic carbon cycle globally. Abstract: EPS (exopolymers) play a central role in global carbon cycling due to huger amount in aquatic environment, and PFOS (Perfluorooctane sulfonate) is also ubiquitous and persistent pollutant. Whether and how can PFOS of environmental concentrations affect behavior and fate of EPS was unclear. In this study, for the first time interaction between lake EPS and PFOS of environmental concentrations was visually probed by AFM-IR technique. It was found that EPS could effectively trap PFOS and the latter of environmental concentrations could trigger nanoscale reassembly of the former. Sandwiched PFOS-EPS nanostructures were formed via supramolecular interaction between EPS and PFOS, confirmed by fluorescence quenching titration and FTIR spectroscopy. The PFOS microlayers sandwiched in EPS was proven to be a light shield that could protect EPS from photodegradation because of its high reflectivity and nearly zero absorbance of UV-Vis light. The light shielding effect of PFOS was confirmed by evidences from photodegradation experiments, including change of concentrations of ions released and molecular weight distribution patterns. These novel findings provided valuable information for deep insight into environmental behavior of PFOS and its effects on biogeochemical carbon cycle of biopolymers in global waters. Graphical abstract: Image, graphical abstract